The antifungal effect of Jacquinia macrocarpa plant extracts on the growth of Aspergillus flavus, A. parasiticus and Fusarium verticillioides - Daniel Fernando Valenzuela-Cota (Revista Mexicana de Micología, 2014)
The aim of this study was to evaluate the effect of fractions obtained from the plant Jacquinia macrocarpa against phytopathogenic fungi Aspergillus flavus, A. parasiticus and Fusarium verticillioides. The powder of the dried plant materials was extracted with methanol (70 % v/v) and partitioned with hexane, ethyl acetate, and n-butanol. The most active fraction against the radial growth of the fungi was further fractionated by silica gel chromatography. The fraction from J. macrocarpa partitioned in n-butanol (BF) showed the highest antifungal activity against the three fungi. Sub-fraction F5.4 completely inhibited the growth of F. verticillioides, whereas the radial growth of A. flavus and A. parasiticus was inhibited 70 % and 64 %, respectively. Spores germination of A. parasiticus and F. verticillioides was inhibited 7.8 % and 11.8%, respectively. The lengths and diameters of hyphae of the three fungi were smaller than those of controls. Spore diameters of the Aspergillus species were reduced, while spores of F. verticillioides were not affected. The spore viability of A. flavus, A. parasiticus and F. verticillioides was reduced 40.7 %, 44.8 % and 46.3 %, respectively. Fraction F5.4 significantly inhibited the development of the three fungi, mainly F. verticillioides.